Managerial competencies and supply chain performance of relief aid organizations in western Uganda - Aryatwijuka, Wilbroad; Kamukama, Nixon; Frederick, Nsambu Kijjambu; Rukundo, Aloysius (American Journal of Supply Chain Management, 2020)
Purpose-The paper presents the influence of managerial competencies on supply chain performance of relief aid organizations in western Uganda. Methods-The study employed a cross-sectional and quantitative research design comprising 105 relief aid organizations operating in western Uganda. Data was analyzed using SPSSv22, to generate descriptive statistics, run correlation and hierarchical regression analysis. Findings-The findings showed a positive significant influence of managerial competencies on supply chain performance of relief aid organizations in western Uganda. Limitations-The study did not examine the influence of other factors such as the other supply chain enablers which include infrastructure on humanitarian supply chain performance. The focus was on the influence of managerial competencies on supply chain performance. Unique contribution to practice and policy- relief aid organizations should emphasize attracting, training and retaining staff with professional, social and personal competencies to ensure efficient delivery of relief supplies.
Keywords: Managerial competencies; Supply chain performance; Relief aid organizations.